Prediction of problems related to TIC in general service organizations using a neural network (2022)
This article shows the efficiency of implementing a Help Desk Application with a predictive model for the definition of a catalog of services, with the execution of good practices for the management of technological services through a quality standard to guarantee these services. Based on that, the general services company attempts to resolve the requests andrequirements of users through application, keeping the life cycle of each incident centralized. This Help Desk system wasdeveloped using the PHP programming language, with the HTML5 structure, its CSS styles defined by Bootstrap and its MYSQL database engine. Thanks to the creation of an entity-relationship model suitable for the needs of the company, a ticket management module, user module, manual module and a descriptive analysis module of the tickets found in the base.